Implementasi Kebijakan Penertiban Reklame Berdasarkan Peraturan Daerah Kota Serang Nomor 3 Tahun 2021 Tentang Penyelenggaraan Reklame - Putri Oktaviani; Rahmawati (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study focuses on the enforcement of billboards in Serang City as outlined in the Regional Regulation of Serang City Number 3 of 2021 concerning Billboard Management. The implementation still faces various issues in the field, such as an ineffective system for recording violations of billboards, a lack of coordination among the relevant agencies, low legal awareness among billboard operators, and suboptimal enforcement of sanctions. The researcher examines these issues using the public policy implementation theory proposed by Van Meter and Van Horn. The purpose of this study is to describe and analyze the implementation of Regional Regulation Number 3 of 2021 on Billboard Management, specifically focusing on enforcing billboard regulations in Serang City. The researcher employs a descriptive qualitative method, acting as the primary instrument for data collection, which is carried out through observation, interviews, and documentation studies. Data analysis uses the Miles and Huberman model, with data validity tests conducted through triangulation and member checking. The results indicate that the implementation of Regional Regulation Number 3 of 2021 on Billboard Management in the case study of billboard enforcement has not been carried out optimally. Therefore, it is necessary to strengthen resource capacity, improve inter-agency coordination, conduct comprehensive socialization to business actors and the community, develop an integrated data system, and enforce sanctions firmly and consistently.